Féminismes africains: une histoire décoloniale : recueil d'entretiens - Dieng, Rama Salla (Présence africaine éditions, 2021)
"Ce recueil d'entretiens est conçu comme une série de conversations avec une vingtaine d'activistes, universitaires féministes en majorité d'Afrique et de sa diaspora. Ces dialogues, conçus dans le but de décentrer la production de connaissance sur les féminismes en Afrique dans une perspective décoloniale, portent sur leurs pratiques, philosophies, aspirations, défis et joies féministes. Il en ressort des interviews qui, au fur et à mesure qu'elles se disent, esquissent une mosaïque fascinante de jeunes hommes et de femmes aux profils, âge, genre, orientation sexuelle, classe, nationalité et parcours professionnels certes variés, mais unis par la passion d'une Afrique où règne davantage d'équité et de justice sociale !"–Page 4 de la couverture.
Section: 219 pages ; 18 cm
Keywords: 2000 à aujourd'hui; afrique; afro-féminisme; approches et analyses; cours; discipline; développement international; féminisme africain; histoire et politique; intersectionnalité; justice sociale; militance; pol4022; premier cycle; périodes historiques; relations internationales; régions géographiques; science politique; science politique et droit; thématiques

Identifications homosexuelles, construction identitaire et tensions postcoloniales entre le Cameroun et la France - Awondo, Patrick (L’Espace Politique, 2011)
L’article problématise la circulation de l’« identité homosexuelle » dans l’entre-deux de l’Occident et de l’Afrique. À partir de l’exemple camerounais, il montre comment des « tensions postcoloniales » parasitent le débat autour de l’homosexualité en se cristallisant notamment sur l’affrontement symbolique entre ordres moraux opposés. Au-delà des identifications sexuelles, l’analyse aborde aussi la situation des individus qui tentent par la migration d’échapper au régime de contrainte camerounais et se retrouvent dans la posture de « réfugié (homo)sexuel » en France, sans que pour autant la question de leur « identité » sexuelle soit « résolue ».
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; afrique; approches et analyses; cameroun; cours; discipline; europe; france; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Mondialisation et migrations féminines internationales, L’esclavage au cœur de la modernité - Ouali, Nouria (Les cahiers du CEDREF, 2003)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; afrique; afrique du nord; approches et analyses; belgique; cours; discipline; droit des femmes*; europe; inégalités; justice sociale; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

The Native and the Refugee - Peterson, Matt; Rasamny, Malek (The Native and the Refugee)
A multi-media project profiling the spaces of the Indian reservation and Palestinian refugee camp: spaces of exception whose position in the struggle for native and Palestinian autonomy are essential. The Native and the Refugee will culminate in a feature-length documentary film.
Keywords: afrique; amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; camps de réfugiés; cours; discipline; documentaire; gaza; justice sociale; militance; palestine; pol5480; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences